2020
DOI: 10.3390/atmos11101137
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Outbreak on Air Quality in Korea

Abstract: The COVID-19 pandemic has led countries to take action, which has included practicing social distancing or lockdown. Many cities are experiencing air quality improvements due to human activity restrictions. The purpose of this study was to compare the air quality between 2020 and the previous three years, focusing on the two cities (Seoul and Daegu) where coronavirus is spreading the fastest in Korea. Significant decreases in PM2.5, PM10, CO, and NO2 were observed in both cities. In particular, compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 35 publications
6
33
0
Order By: Relevance
“…Daegu, which showed the second largest decrease (in %) in the upper quartile of the daily-mean PM 2.5 concentration (Fig. 2(a)), had the largest decrease in CO concentration (−28.6%) going from pre-SD to SD, which is also in line with Seo et al (2020).…”
Section: Inter-city Comparisonssupporting
confidence: 68%
“…Daegu, which showed the second largest decrease (in %) in the upper quartile of the daily-mean PM 2.5 concentration (Fig. 2(a)), had the largest decrease in CO concentration (−28.6%) going from pre-SD to SD, which is also in line with Seo et al (2020).…”
Section: Inter-city Comparisonssupporting
confidence: 68%
“…A comparison of the average CO levels revealed that a 39% reduction occurred at Alphington (Katestone, 2020b , c ). In Seoul, Korea, PM 2.5 showed a considerable drop of 36% in March 2020 compared to the same time of 2017–2019 (Seo et al 2020 ). A decrease of 20.6% in PM 2.5 levels in the USA was also observed in March 2020 relative to March 2019.…”
Section: Indirect Impacts Of Covid-19 On the Environment Of The Statementioning
confidence: 99%
“…Data processing was performed on raw concentration values, without Due to the progressive enforcement of the restrictive measures since the last week of February, atmospheric emissions varied from day to day, also depending on the pollutants in emissions, compared to their typical values (Supplementary Materials Figure S1). Estimates developed by the Environmental Agency of Lombardia [32] for NOx during the weeks from 9 March to 26 April indicated reductions around a regional average value of about −36%, but ranging between −44% (6)(7)(8)(9)(10)(11)(12) and −20% (9)(10)(11)(12)(13)(14)(15); however, emission reductions in large urban areas in April were −50%, and sometimes −60%. The main contributor to these decreases was the reduction in emissions from road traffic, which was estimated to be around −65% over the entire lockdown period, but −75% at the beginning of April.…”
Section: A B Cmentioning
confidence: 99%
“…Recently, a number of papers have been published reporting the changes in concentration levels for certain pollutants in different areas worldwide, where light or heavy restrictive measures have been implemented [5]. Most of these works refer to China [6][7][8], Korea [9][10][11], India [12], Central [13,14], and South-East Asia [15], but also to Western European countries [16][17][18], Africa [19,20], and North and South America [21][22][23]. The few studies related waste treatment each accounted for 1% of the total annual emissions (about 185 Gg year -1 ).…”
Section: Introductionmentioning
confidence: 99%